Off to the side a memoir - Harrison, Jim (Atlantic Monthly Press, 2002)
The novelist and poet chronicles growing up in Michigan during the Depression and Second World War, his love of literature, his career as a screenwriter and author, and the obsessions that have shaped his life.
Keywords: Harrison, Jim <1937->; Harrison, Jim -- 1937-2016; Geschichte 1900-2000; Authors, American -- 20th century -- Biography; Autobiografie; Biografie